The fault in our stars - Green, John 1977- (New York Penguin Group, 2012)
Sixteen-year-old Hazel, a stage IV thyroid cancer patient, has accepted her terminal diagnosis until a chance meeting with a boy at cancer support group forces her to reexamine her perspective on love, loss, and life. Despite the tumor-shrinking medical miracle that has bought her a few years, Hazel has never been anything but terminal, her final chapter inscribed upon diagnosis. But when a gorgeous plot twist named Augustus Waters suddenly appears at Cancer Kid Support Group, Hazel's story is about to be completely rewritten.
According to author John Green, The Fault In Our Stars was inspired by his friendship with Esther Earl, who "redefined the process of dying young for me." (December 2012 Good Reads interview, http://www.goodreads.com/interviews/show/828.John_Green). He cautions his readers not to take the novel too literally however, stating that he doesn't "want people conflating Esther with Hazel (they're very different), and it's extremely important to me that I not claim to be telling Esther's story. Esther's story belongs to Esther and to her family." (John Green's tumblr, August 2, 2012 http://fishingboatproceeds.tumblr.com/post/28557373623/everybody-was-told-to-make-a-funny-face-but-i). Esther's story is told in the 2014 posthumous memoir This Star Won't Go Out : the Life and Words of Esther Grace Earl.
"Penguin books."--Title page.
Young Adult.
Accelerated Reader
Keywords: Cancer in adolescence -- Juvenile fiction; Terminally ill -- Juvenile fiction; Terminally ill children -- Juvenile fiction; Love stories; Young women -- Conduct of life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Sick -- Juvenile fiction; Physicians -- Juvenile fiction; Youth -- Death -- Juvenile fiction